Dairy Product Consumption and Bladder Cancer Risk in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cohort - Xu, Xin (Frontiers in Nutrition, 2020)
Evidence has suggested that dairy product consumption lowers the risk of several cancers, but these benefits may not occur with bladder cancer. In a cohort of 101,721 subjects in the Prostate, Lung, Colorectal, and Ovarian (PLCO) Cancer Screening Trial, we analyzed the effects of dairy product intake on bladder cancer risk using Cox proportional hazards regression. After a median of 12.5 years of follow-up, 776 new cases of bladder cancer were identified. We found no statistically significant association between total milk intake and bladder cancer risk. The multivariate-adjusted hazard ratio (HR) of bladder cancer for participants in the highest category of total milk intake compared with those in the lowest category was 1.13 (95% CI: 0.92–1.40; p for trend = 0.436). Among individual dairy foods, no statistically significant association was observed for a broad range of dairy products, including whole milk, 2% milk, 1% milk, skim milk, yogurt, regular butter, low fat butter, regular cheese, low fat cheese, and no fat cheese. These associations were not modified by smoking status (p for interaction > 0.05). In conclusion, findings from this large prospective analysis do not support an inverse association between dairy product consumption and bladder cancer risk.